Gen-Q: Kolaborasi Dakwah dan Pendidikan dalam Membentuk Generasi Qur'ani di Bonto Tallasa Maros: Gen-Q: The Collaboration of Islamic Da’wah and Education in Cultivating A Qur’anic Generation in Bonto Tallasa Maros - Maryam, Maryam; Nuraeni Novira (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The Community Service Program (PkM) in the field of Education and Da'wah aims to strengthen Al-Qur'an literacy and shape children's religious character through the Gen-Q program in Bonto Tallasa Village, Maros. The implementation method consists of guidance in reading the Al-Qur'an, gradual memorization, educational activities, program evaluation, as well as adjustment strategies due to the heterogeneity of participants' ages and abilities. Data was obtained through direct observation during activities and documentation of the implementation of Gen-Q. PkM results show increased motivation for learning the Qur'an in children, increased participation in TPA/TPQ activities on weekends, and the emergence of a more interactive Qur'an learning environment. This program contributes to providing an applicable da'wah-education collaboration model for developing the Al-Qur'an in local communities, as well as confirming the importance of an adaptive approach in forming the Qur'anic generation at the community level.